1987
DOI: 10.1007/bf01402366
|View full text |Cite
|
Sign up to set email alerts
|

Cavernomas of the central nervous system: Clinical syndromes, CT scan diagnosis, and prognosis after surgical treatment in 25 cases

Abstract: We present our clinical experience and the results of surgical management with 25 cavernomas of the CNS, treated in our hospital in the last 10 years. The location of the lesion assessed by clinical and CT scan examinations, proved to be the most significative factor determining the prognosis of cavernomas of the CNS, after surgical removal. The symptoms started in most of the cases in the third decade of life. 19 cases were located in the cerebral hemispheres and produced three well defined clinical syndromes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
7

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(31 citation statements)
references
References 14 publications
2
22
0
7
Order By: Relevance
“…11,39,51,52 In most series, however, an equal distribution between the sexes 13,24,26,31,40,43,48,53 has been reported, and this was also the case in ours. Some authors have suggested a higher propensity for bleeding episodes in female patients, 16,48 often during pregnancy.…”
Section: Age and Sex Of The Patientssupporting
confidence: 74%
See 1 more Smart Citation
“…11,39,51,52 In most series, however, an equal distribution between the sexes 13,24,26,31,40,43,48,53 has been reported, and this was also the case in ours. Some authors have suggested a higher propensity for bleeding episodes in female patients, 16,48 often during pregnancy.…”
Section: Age and Sex Of The Patientssupporting
confidence: 74%
“…23,46 Perilesional hypodensity can be found, and it may represent edema, hemosiderin, or even atrophy. 23,52 The CMs can be present as a cystic lesion that is isodense or hypodense on CT scans, with or without a wall nodule, and consequently, differentiation from posterior fossa gliomas is very difficult based on CT findings alone. 7,23,25 All patients in our series underwent CT scanning.…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
“…Kanama olmuş ise hiperdens gö-rünüm ile birlikte çevresel ödem ve kitle etkisi tespit edilir. Kontrastlı çalışmalarda zayıf bir kontrast tutulumu görülebilir (10,13). Klinik olgularımızın 4'ününde de kompüterize tomografilerinde kanamaya bağlı hiperdens görünüm elde edilmiştir.…”
Section: Discussionunclassified
“…Cerrahi eksizyonun amacı; kanama sonucu gelişen hematoma bağlı gör-me keskinliğinin giderilmesi, lezyonun histopatolojik natürünün tespit edilmesi ve yeniden kanamayı önlemeye yöneliktir (1,2,4,8,10,11,12,13,14,15). Orbital kavernöz anjiomlarda gelişen görme kaybının giderilmesi için cerrahi girişim geciktirilmemelidir.…”
Section: Discussionunclassified
“…Patients frequently are asymptomatic (40,70%) (3, 11, 12); symptomatic subjects typically present between ages 20 and 40, although symptoms can begin at any age (6,7,13). Patients commonly present with seizures (7, 14), brain hemorrhage (3,6,11,(13)(14)(15)(16)(17), focal neurological deficits (6, 11-13, 15), or headaches. Risk of bleeding from these lesions is in part dependent on age and the prior occurrence of hemorrhage from the same lesion (15,18).…”
mentioning
confidence: 99%